Observaciones sobre el cuaternario en el valle del rio negro-guayuriba y piedemonte llanero al oriente de bogotá (1985)
A brief description of the Quaternary deposits of the Negro-Guayuriba river valley is presented here, along with some comments on its geomorphologic evolution, taking into consideration the existence of a direct relationship between these deposits, all which confirms that past glacial activity and intense tectonism are responsible for the present morphology and for the origin of source areas and deposits, besides providing the systems with sufficient energy to transfer the loads which originated the deposits. The Quaternary deposits have been classified as glacial deposits, terraces, alluvial deposits, coluvial deposits, mud flows and slide deposits.